2020
DOI: 10.1097/brs.0000000000003190
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical Study and Clinical Significance of the Sinuvertebral Nerves at the Lumbar Levels

Abstract: Study Design. A dissection-based study of 10 embalmed human cadavers. Objective. The purpose of this study was to describe the sinuvertebral nerves at the lumbar level and to discuss their possible clinical significance. Summary of Background Data. Discogenic low-back pain is mediated by the sinuvertebral nerves. However, the detailed descriptions of the sinuvertebral nerves at the lumbar level are lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 18 publications
4
23
0
Order By: Relevance
“…They found that the nerves were adjacent to the blood vessels and that they enter posteriorly via the basivertebral foramen and cluster in the vertebral center. These sinuvertebral nerves, which likely accompany the nutrient artery into the vertebral body, are an important potential source and target for treatment [46]. This is in agreement with what was previously believed.…”
Section: Anatomysupporting
confidence: 89%
See 2 more Smart Citations
“…They found that the nerves were adjacent to the blood vessels and that they enter posteriorly via the basivertebral foramen and cluster in the vertebral center. These sinuvertebral nerves, which likely accompany the nutrient artery into the vertebral body, are an important potential source and target for treatment [46]. This is in agreement with what was previously believed.…”
Section: Anatomysupporting
confidence: 89%
“…Zhao et al shed further light on the anatomy of the sinuvertebral nerves within the lumbar vertebrae [46]. The authors found that the sinuvertebral nerves divide into a deputy branch and main trunk.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Removal of herniated nucleus pulposus: relieving mechanical compression and in ammatory stimulation of nerve roots. (2) Denervation of annulus brosus by bipolar electrocoagulation: Li et al (31) have shown that the SVN originates from the posterolateral edge of the intervertebral disc to the spinal canal, and the accessory branches of the SVN enter directly into the posterolateral margin of the intervertebral disc. Among them, 55.8% of the main trunk of the SVN originates from the spinal ganglion of the posterior root of the spinal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In a normal intervertebral disc, sinuvertebral nerves are confined to the outer third of the annulus fibrosus 36 . However, in degenerated or injured discs, sinuvertebral nerves grow along a fissure or tear within discs 37 .…”
Section: Discussionmentioning
confidence: 99%